2022
DOI: 10.3389/fcell.2022.860344
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and its Role in Gastric Cancer

Abstract: Gastric cancer (GC) is the fifth most common cancer and the third leading cause of cancer-related deaths worldwide. Currently, surgery is the treatment of choice for GC. However, the associated expenses and post-surgical pain impose a huge burden on these patients. Furthermore, disease recurrence is also very common in GC patients, thus necessitating the discovery and development of other potential treatment options. A growing body of knowledge about ferroptosis in different cancer types provides a new perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 115 publications
0
30
0
Order By: Relevance
“…Ferroptosis is a newly identified programmed cell death, typically characterized by free iron overload and lethal phospholipid peroxide generation. Increasing evidence has demonstrated that inducing ferroptosis represents a promising therapeutic strategy that preferentially targets iron-rich cancer cells such as HCC [ 67 , 68 ], NSCLC [ 69 ], PDAC [ 70 ], leukemia [ 38 ] and GC [ 71 , 72 ], and provides insights into reversing drug resistance in cancers. The mitochondrial electron transport chain is responsible for ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a newly identified programmed cell death, typically characterized by free iron overload and lethal phospholipid peroxide generation. Increasing evidence has demonstrated that inducing ferroptosis represents a promising therapeutic strategy that preferentially targets iron-rich cancer cells such as HCC [ 67 , 68 ], NSCLC [ 69 ], PDAC [ 70 ], leukemia [ 38 ] and GC [ 71 , 72 ], and provides insights into reversing drug resistance in cancers. The mitochondrial electron transport chain is responsible for ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…This is also a hallmark of ferroptosis ( Conrad and Pratt, 2019 ). This reaction not only damages lipids and proteins but also causes oxidative damage to DNA, including DNA base modifications and DNA strand breaks ( Gu et al, 2022 ; Wu et al, 2022 ). While an iron overload does not always induce ferroptosis, it will enhance cell death when it occurs.…”
Section: The Underlying Mechanisms Of Ferroptosis In Ichmentioning
confidence: 99%
“…Ferroptosis plays a role in the development and progression of many diseases, including cancer, necroinflammatory disorders, and many organ damages and degenerative changes ( Jiang et al, 2021 ). Previous studies have revealed the important role of ferroptosis in GC ( Zhang et al, 2020 ; Liu et al, 2021 ; Gu et al, 2022 ). Ferroptosis plays an important regulatory role in the development of malignant tumors such as proliferation, invasion and metastasis of GC ( Guan et al, 2022 ; Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%